(untitled) (Research, Society and Development, 2021)
Introduction: The clinical course of COVID-19 presents clinical manifestations that range from no symptoms to severe pneumonia, cardiac or brain damage. Objective: To analyze the epidemiological and clinical profile of patients with COVID-19 admitted to the ICU of a Public Hospital in Teresina-PI. Methods: it has a descriptive and retrospective design performed by analyzing medical records, including patients with COVID-19 who were admitted to the ICU between April and October 2020, discharged from hospital or evolved to death, over 18 years old, of both sexes and those that highlight with incomplete data are excluded. Results: 240 patients were included and most were elderly (63.9 ± 15.9 years), male (55%), married (55.8%) and from the countryside of Piauí (46.7%) who have comorbidities such as SAH (55.6%) and DM (33.9%). Conclusion: This is a serious pathology that involves long hospital stays, often requiring intubation and IMV, in addition to unconventional interventions, such as pronation.